The public administration of territorial seas: Ukrainian case - Кормич, Борис Анатолійович; Кормич, Борис Анатольевич; Kormych, Borys A.; Аверочкіна, Тетяна Володимирівна; Аверочкіна, Т. В.; Аверочкина, Татьяна Владимировна; Averochkina, Tetiana V.; Гаверський, Віталій Валерійович; Гаверський, В. В.; Гаверский, Виталий Валерьевич; Gaverskyi, Vitaliy V.; Кормич, Б. А. (Springer, 2020)
The article evaluates the modern doctrine of territorial sea administration, given the experience of Ukraine. The article analyzes the formation of the coastal state's legal and institutional rights and obligations in accordance with international law. It is also studied how such regulation has been formed as well as its interaction with other administrative and legal regulations, which function in a given maritime zone. Public administration of territorial seas, despite the significant role of international legal regulation, fully relies on the institutional and organizational ability of the state to effectively exercise its jurisdiction in the relevant marine areas. For instance, Ukraine is taking steps to fulfill its obligations to ensure the safety of navigation and conduct rescue operations in its area of responsibility in accordance with international agreements. Ukraine’s experience in administering territorial sea after the illegal annexation of Crimea is studied, and the pros and cons are revealed of modern concepts in this area in the context of hybrid conflicts.

У статті дається оцінка сучасній доктрині управління територіальним морем, враховуючи досвід України. У статті проаналізовано формування в прибережній державі юридичних та інституційних прав та обов’язків відповідно до міжнародного права. Також вивчається, як було сформовано таке регулювання, а також його взаємодія з іншими адміністративно-правовими нормативними актами, які функціонують у даній морській зоні. Державне управління територіальними морями, незважаючи на значну роль міжнародно-правового регулювання, повністю покладається на інституційну та організаційну здатність держави ефективно здійснювати свою юрисдикцію у відповідних морських районах. Наприклад, Україна вживає заходів для виконання своїх зобов'язань щодо забезпечення безпеки судноплавства та проведення рятувальних робіт у зоні відповідальності відповідно до міжнародних угод. Вивчається досвід України в управлінні територіальним морем після незаконної анексії Криму та розкриваються плюси і мінуси сучасних концепцій у цій галузі в контексті гібридних конфліктів.

В статье дается оценка современной доктрине управления территориальным морем, учитывая опыт Украины. В статье проанализировано формирование в прибрежном государстве юридических и институциональных прав и обязанностей в соответствии с международным правом. Также изучается, как было сформировано такое регулирование, а также его взаимодействие с другими административно-правовыми нормативными актами, которые функционируют в данной морской зоне. Государственное управление территориальными морями, несмотря на значительную роль международно-правового регулирования, полностью возлагается на институциональную и организационную способность государства эффективно осуществлять свою юрисдикцию в соответствующих морских районах. Например, Украина принимает меры для выполнения своих обязательств по обеспечению безопасности судоходства и проведение спасательных работ в зоне ответственности в соответствии с международными соглашениями. Изучается опыт Украины в управлении территориальным морем после незаконной аннексии Крыма и раскрываются плюсы и минусы современных концепций в этой области в контексте гибридных конфликтов.
Kormych B., Averochkina T., Gaverskyi V. The public administration of territorial seas: Ukrainian case / B. Kormych, T. Averochkina, V. Gaverskyi // International Environmental Agreements: Politics, Law and Economics. – V. 20 (3). – Springer, 2020. – P. 577-595.
Keywords: Coastal state jurisdiction; Marine environment; Maritime zone; Public administration; Territorial sea Ukraine; юрисдикція прибережної держави; морське середовище; морська зона; державне управління; територіальне море; Україна; юрисдикция прибрежного государства; морская среда; морская зона; государственное управление; территориальное море; Украина; Research Subject Categories::LAW/JURISPRUDENCE